Peran digital marketing dalam media sosial Instagram Bakso Mbah’e Solo untuk membangun brand awarness - A’yun, Diah Qurrota (Maliki Interdisciplinary Journal, 2024)
Currently, accessing information has become quicker and easier. One way to obtain information is through social media, including platforms like Instagram. "Bakso Mbah’e Solo" is a culinary business that hasn’t fully utilized social media, particularly Instagram, to maximize branding efforts, resulting in a lack of brand awareness. Recognizing this challenge, the researcher engaged actively to address this issue through observational approaches and active involvement. This approach is well-suited to the situation at hand. Research findings highlight that crafting content via social media serves as an effective marketing tool to reinforce brand recognition. Enhancing brand awareness is crucial for business owners to reach a wider audience. To reach this audience, companies must understand audience needs, conduct competitor analysis, observe social media trends, and create content. This research is expected to offer benefits and implications, including increased insights, information, and knowledge for stakeholders. Additionally, it’s anticipated that this study will serve as a catalyst for further exploration of aspects within the realm of digital marketing that haven’t been addressed in this research.